The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1002/micr.20715
|View full text |Cite
|
Sign up to set email alerts
|

Needing a large DIEAP flap for unilateral breast reconstruction: Double‐pedicle flap and unipedicle flap with additional venous discharge

Abstract: This retrospective study showed that both options of raising a large DIEAP flap for unilateral breast reconstruction, namely unipedicled flap based on large medial perforator/s plus additional venous discharge or double-pedicle flap, are safe. Preoperative examination of the dominant perforator/s with CDS and/or MDCT is mandatory in both cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Rothenberger et al suggested that the supercharging of the contralateral SIEV leads to an improved venous outflow particularly in flaps containing larger proportions of the contralateral zones ( 58 ). Also in patients with the need of a large flap it was possible to use a unipedicle four-zone DIEP flap with an additional anastomosis of the SIEV, if the superficial venous system showed strong vascular connections between right and left hemiabdomen ( 59 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rothenberger et al suggested that the supercharging of the contralateral SIEV leads to an improved venous outflow particularly in flaps containing larger proportions of the contralateral zones ( 58 ). Also in patients with the need of a large flap it was possible to use a unipedicle four-zone DIEP flap with an additional anastomosis of the SIEV, if the superficial venous system showed strong vascular connections between right and left hemiabdomen ( 59 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recipient vessel for the SIEV can be any vein with an adequate caliber and length. Described in the literature are, among others, the thoracoacromial vein ( 60 , 61 ), the lateral thoracic vein ( 12 , 62 , 63 ), the circumflex scapular vein ( 5 , 64 ), the thoracodorsal vein, the basilic ( 65 ) und cephalic vein ( 6 , 17 , 66 , 67 ), the external jugular vein ( 9 , 59 ), the internal mammary vein ( 7 , 11 , 68 70 ) and its perforators ( 71 ). Rohde et al and later Sbitany et al described a flap salvage technique by anastomosing the ipsilateral SIEV to a venae comitantes of the deep inferior epigastric pedicle ( 72 , 73 ).…”
Section: Discussionmentioning
confidence: 99%
“…There are various surgical techniques to recruit the whole flap, including double pedicle, stacked flaps, and other methods to increase flap projection. 15 18 All these will increase the complexity of the surgery and, thereby put the patient at greater risk for complications. The patients at our institution often prefer to keep their original breast size.…”
Section: Discussionmentioning
confidence: 99%
“…Bipedicled DIEP flaps have also been described in several different compositions (Agarwal & Gottlieb, 2007;Beahm & Walton, 2007;Murray, Wasiak, Rozen, Ferris, & Grinsell, 2015;Salgarello, Barone-Adesi, Sturla, Masetti, & Mu, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Introducing a second vascular pedicle into the flap may enhance its perfusion to an additional volume of tissue included in the flap (Murray et al, 2015;Salgarello et al, 2010;Zelter, Andrades, & Hamdi, 2011). Bipedicled free flap uses two vascular pedicles (minimum of four microvascular anastomoses) to enable harvesting entire lower abdomen.…”
Section: Introductionmentioning
confidence: 99%